The absorption of a weak electromagnetic Wave by free electrons in semiconductor superlattices in the presence of a quantizing magnetic field - Bau, Nguyen Quang; Toan, Nguyen The; Navy, Chhoum (VNU Journal of Science: Natural Sciences and Technology; Vol 12 No 2, 1996)
Abstract